2015
DOI: 10.1016/j.immuni.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-DNA Composites of Bacterial Biofilms Stimulate Autoimmunity

Abstract: SUMMARY Research on the human microbiome has established that commensal and pathogenic bacteria can influence obesity, cancer, and autoimmunity through mechanisms mostly unknown. We found that a component of bacterial biofilms, the amyloid protein curli, irreversibly formed fibers with bacterial DNA during biofilm formation. This interaction accelerated amyloid polymerization and created potent immunogenic complexes that activated immune cells, including dendritic cells, to produce cytokines such as Type I int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
241
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 196 publications
(254 citation statements)
references
References 84 publications
(97 reference statements)
8
241
1
4
Order By: Relevance
“…Some recent information pointed out that DNA might also play this role. Direct interaction of DNA with two major bacterial amyloids, curli and PSMs, reveals its role as a nucleator of amyloid polymerization (80). In the case of curli fibers, Gallo et al (80) showed that Salmonella curli fibers bind tightly to extracellular DNA (eDNA), protecting it from degradation by DNases.…”
Section: Role Of Biofilm-associated Extracellular Dna In Amyloid Polymentioning
confidence: 99%
See 2 more Smart Citations
“…Some recent information pointed out that DNA might also play this role. Direct interaction of DNA with two major bacterial amyloids, curli and PSMs, reveals its role as a nucleator of amyloid polymerization (80). In the case of curli fibers, Gallo et al (80) showed that Salmonella curli fibers bind tightly to extracellular DNA (eDNA), protecting it from degradation by DNases.…”
Section: Role Of Biofilm-associated Extracellular Dna In Amyloid Polymentioning
confidence: 99%
“…In the case of curli fibers, Gallo et al (80) showed that Salmonella curli fibers bind tightly to extracellular DNA (eDNA), protecting it from degradation by DNases. Furthermore, addition of three different types of nucleic acids (synthetic oligonucleotide, Salmonella genomic DNA, or eukaryotic DNA) indistinctly reduced the lag phase for curli fiber polymerization, suggesting a mechanism by which DNA molecules trigger the assembly of CsgA monomers into highly stable complexes that would provide stability to Salmonella enterica serovar Typhimurium biofilms (80).…”
Section: Role Of Biofilm-associated Extracellular Dna In Amyloid Polymentioning
confidence: 99%
See 1 more Smart Citation
“…Salmonella biofilm ECM components have been determined and include proteins (curli fimbriae and BapA), polysaccharides (extracellular DNA, cellulose, O-antigen capsule, colanic acid [in nontyphoidal serovars], and Vi antigen [ViAg] [in serovars Typhi, Dublin, and Paratyphi C]) (7,(13)(14)(15)(16)(17). Individual mutations in these ECM factors have been tested by various groups for their roles in biofilm formation, and some have also been examined for phenotypes in vertebrate models of infection (18)(19)(20)(21)(22)(23)(24). However, combinations of mutations and direct comparisons in vitro or in vivo have not been made.…”
mentioning
confidence: 99%
“…At least 40% of bacterial species produce amyloid-like proteins that share a quaternary structure, as well as physical and immunological properties, with human amyloids associated with complex diseases such as Alzheimer's disease, prion diseases, and type II diabetes. Hence, bacterial amyloids present in the biofilm extracellular matrix, where they can bind extracellular DNA (eDNA), could induce inflammation and production of anti-double-stranded DNA (anti-dsDNA) as well as antichromatin antibodies, potentially contributing to the progression of autoimmunity (30). In his work, Steven Goodman (Nationwide Children's Hospital, Columbus, OH) has found that targeting the DNABII family of proteins required for the maintenance of eDNA structure can prevent biofilm formation by nontypeable Haemophilus influenzae, P. aeruginosa, S. aureus, and Burkholderia cenocepacia.…”
Section: New Insights Into Antimicrobial Tolerance and Novel Targetsmentioning
confidence: 99%